Analisis Framing Kompas.Com Dan Detik.Com Dalam Pemberitaan Kekerasan Seksual Di Indonesia - Muhammad Fahmi Al Farizi; Julyanto Ekantoro; Tira Fitriawardhani (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Public perception of sexual violence cases is influenced by media coverage, which shapes social reality through framing processes. This study aims to analyze and compare the framing of Kompas.com and Detik.com in reporting sexual violence cases in Indonesia. Robert N. Entman's framing model was applied through four elements: problem definition, causal interpretation, moral evaluation, and treatment recommendation. These media were selected due to their significant public reach and different reporting characteristics, with Kompas.com emphasizing contextual analysis and Detik.com prioritizing speed and concise information delivery. This qualitative study employed framing analysis on ten news articles selected through purposive sampling from January to December 2024. The findings indicate that Kompas.com highlights context, victim perspectives, and educational aspects, while Detik.com focuses on facts and chronology. Differences in framing are influenced by editorial characteristics and news presentation strategies. This study contributes to understanding media construction of sexual violence issues and encourages ethical, victim-sensitive journalism.